Housing Modernization and Urban Planning in Vilnius: 1919–1943 - Drėmaitė, Marija (Lietuvos istorijos studijos, 2022)
Housing modernization played a key role in interwar European urban planning, as it was used to build a new type of healthy and comfortable residential area. This question is also relevant in the case of the city of Vilnius, since from 1919 to 1939 the area of the city did not increase – its limits covered an area of 10 400 hectares, which was approved in 1919. This means that the modernization of housing and related urban planning in Vilnius had to take place in a different way than it had in the rapidly growing cities of East Central Europe, where the growth of a city’s area was stimulated by newly built residential suburbs. In this paper, residential architecture of Vilnius in 1919–1943 is studied based on the theory of housing-based urban planning formulated by Yael Alweill and Noa Zemer. Through an examination of how the Greater Vilnius Master Plan (1936–1939) was prepared, the research follows how the construction of modern housing affected urban planning and functional zoning.